1994
DOI: 10.1097/00000658-199409000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Mapping and Sentinel Lymphadenectomy for Breast Cancer

Abstract: ObjectiveThe authors report the feasibility and accuracy of intraoperative lymphatic mapping with sentinel lymphadenectomy in patients with breast cancer. Summary Background DataAxillary lymph node dissection (ALND) for breast cancer generally is accepted for its staging and prognostic value, but the extent of dissection remains controversial. Blind lymph node sampling or level dissection may miss some nodal metastases, but ALND may result in lymphedema. In melanoma, intraoperative lymph node mapping with sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

28
1,318
4
97

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,650 publications
(1,447 citation statements)
references
References 21 publications
28
1,318
4
97
Order By: Relevance
“…Therefore, a tumour-free sentinel lymph node implies the absence of lymph node metastases in the entire lymphatic basin. This sentinel node concept had been previously confirmed by H&E examinations, immunohistochemical study and nonquantitative RT -PCR assays (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998;Kataoka et al, 2000;Manzotti et al, 2001;Branagan et al, 2002;Ishida et al, 2002).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, a tumour-free sentinel lymph node implies the absence of lymph node metastases in the entire lymphatic basin. This sentinel node concept had been previously confirmed by H&E examinations, immunohistochemical study and nonquantitative RT -PCR assays (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998;Kataoka et al, 2000;Manzotti et al, 2001;Branagan et al, 2002;Ishida et al, 2002).…”
mentioning
confidence: 60%
“…In addition, no post-PCR manipulations are required with this method, and quantification and calculation of the results are all automated. Currently, many investigators reported sentinel lymph node biopsy for the diagnosis of axillary lymph node metastases from breast cancer (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998). The sentinel lymph node is the first lymph node to receive drainage from the primary tumours in early stage cancers (Morton et al, 1992).…”
mentioning
confidence: 99%
“…More recently, sentinel lymph node biopsy (SLNB) has been proposed as an alternative method for staging the axilla in women who have early breast cancer with clinically node negative axillae (Giuliano et al, 1994;Veronesi et al, 1997;McIntosh and Purushotham, 1998;Veronesi et al, 1999;Veronesi et al, 2003). The SLN is the first lymph node to receive lymphatic drainage from a tumour.…”
mentioning
confidence: 99%
“…A less invasive method for the assessment of lymph node status is the sentinel lymph node biopsy (SLNB). Thereby, the lymphatic route of tumour cells to the lymph node(s) that primarily drains the tumour and most likely harbours metastatic disease are mapped (Giuliano et al, 1994). The sentinel lymph node (SN) is highly predictive of the histo-pathology of the remaining lymphatic basin and can accurately predict axillary nodal status in at least 98% of cases (Giuliano et al, 1995(Giuliano et al, , 1997.…”
mentioning
confidence: 99%